COVID-19 Outbreak among Healthcare Workers in a Specialty Unit in a Low-Middle Income Setting - Regina E. Oladokun; Babatunde O. Ogunbosi; Oreoluwa E. Morakinyo (International Journal of Medicine and Health Development)
Background: The global impact of the coronavirus disease 2019 (COVID-19) pandemic has strained healthcare workers (HCWs) and services worldwide. As the pandemic evolves, there is a need to assess the patterns, clinical manifestations, and outcomes among HCWs, especially in low-middle income countries where challenges such as inadequate infection prevention and control practices, personal protective equipment, and low diagnostic capacity persist. Objective: To determine the pattern, clinical manifestations, laboratory characteristics, and outcomes of COVID-19 infection among HCWs in a specialty unit in Ibadan, Nigeria. Materials and Methods: A retrospective cohort study was conducted on 107 HCWs over 8 weeks during a COVID-19 outbreak among HCWs in a specialty unit in Ibadan, Nigeria. Data on demographics, clinical characteristics, and laboratory findings were collected using a structured proforma. Severe-acute-respiratory-syndrome-related coronavirus laboratory tests followed the World Health Organization recommendations, with nasopharyngeal swabs obtained for real-time reverse transcription–polymerase chain reaction. Results: Among the HCWs, a 49% COVID-19 positivity rate was found, with cases peaking in the third week. Nurses demonstrated the highest infection rate (36.5%). Fatigue and myalgia were predominant symptoms with 51.9% (P < 0.001) of COVID-19 HCWs reporting both symptoms. Conclusion: The high prevalence of asymptomatic cases highlights the potential role of HCWs as sources of infection for COVID-19, emphasizing the need for stringent infection control measures and continuous support for the well-being of healthcare professionals.